Immune-checkpoint-inhibitor therapy directed against PD-L1 is tolerated in the heart without manifestation of cardiac inflammation in a preclinical reversible melanoma mouse model - Schoenherr, Caroline; Pietzsch, Stefan; Barca, Cristina; Müller, Franziska E.; Bahr, Frauke S.; Kasten, Martina; Zeug, Andre; Erschow, Sergej; Falk, Christine S.; Ponimaskin, Evgeni; Thackeray, James T.; Hilfiker-Kleiner, Denise; et al. (Frontiers in Molecular Medicine, 2025)
Immune-checkpoint-inhibitors (ICI) target key regulators of the immune system expressed by cancer cells that mask those from recognition by the immune system. They have improved the outcome for patients with various cancer types, such as melanoma. ICI-based therapy is frequently accompanied by immune-related adverse side effects (IRAEs). The reversible melanoma cancer mouse model (B16F10 cells stably expressing a ganciclovir (GCV)-inducible suicide gene in C57BL/6N mice: B16F10-GCV) allows chemotherapy-free tumor elimination in advanced disease stage and demonstrates almost complete recovery of the mouse heart from cancer-induced atrophy, molecular impairment and heart failure. Thus, enabling the study of anti-cancer-therapy effects. Here, we analyzed potential cardiac side effects of antibody-mediated PD-L1 inhibition in the preclinical B16F10-GCV mouse model after tumor elimination and 2 weeks recovery (50 days after tumor inoculation). Anti-PD-L1 treatment was associated with improved survival as compared to isotype control (Ctrl) treated mice. Surviving anti-PD-L1 and Ctrl mice showed similar cardiac function, dimensions and the expression of cardiac stress and hypertrophy markers. Although anti-PD-L1 treatment was associated with increased troponin I type 3 cardiac (TNNI3) blood levels, cardiac mRNA expression of macrophage markers and elevated cardiac levels of secreted inflammatory factors compared to Ctrl treatment, both groups showed a comparable density of inflammatory cells in the heart (using CXCR4-ligand 68Ga-Pentixafor in PET-CT and immunohistochemistry). Thus, anti-PD-L1 therapy improved survival in mice with advanced melanoma cancer with no major cardiac phenotype or inflammation 50 days after tumor inoculation. Without a second hit that triggers the inflammatory response, anti-PD-L1 treatment appears to be safe for the heart in the preclinical melanoma mouse model.